Post-exercise cold water immersion on sports performance recovery: A review - Ching Chow, G. C.; Ming Fong, S. S.; Yee Chung, J. W.; Macfarlane. D. J. (Journal of Sports Research, 2015)
Post-exercise cold water immersion (CWI) has recently been developed and applied in professional sports. CWI has become widely accepted for use in sports and is endorsed by various organisations, such as the American College of Sports Medicine (ACSM), the International Amateur Athletic Federation (IAAF), and the National Athletic Trainers` Association (NATA). Specific considerations on the extensive use of CWI in the field of sports, the effects of performance recovery after CWI intervention are noteworthy to be examined. This article aimed to review and summarize reports studying effects of CWI on post-exercise recovery. A comprehensive examination of literature was conducted and the decided databases were reviewed. Positive effects of post-exercise CWI on athletes` endurance performance and perceived recovery were found. The possible reasons relate to the reduction of core temperature and blood redistribution. However, CWI effects on power related performance did not receive a consensus understanding in this review. Cryotherapy is normally used for limiting muscle damages, but post-exercise CWI on alternating blood markers for the muscle damages did not show a clear finding in this review. Particularly, Jadad score analysis in this review shows low on average (average Jadad score = 1.80±1.17) of the quality of the studies. It is necessary to reconsider the application on the previous examination. Further investigation is recommended, specifically on power related recovery and neural transmission alternations using randomized controlled trial with masking design.